2019
DOI: 10.5505/vtd.2019.52533
|View full text |Cite
|
Sign up to set email alerts
|

Medical Profile of Individuals Who Apply to Faculty of Dentistry

Abstract: Tıp alanındaki gelişmeler, sağlık tesislerine erişimin kolaylaşması ve sosyo-ekonomik koşulların daha iyi olması bireylere daha uzun yaşam süresi ve daha iyi bir hayat standardı sağlamaktadır (1). İnsanların sistemik hastalıklara ve ağız sağlığı sorunlarına tedavi arayışları yaşla birlikte artmaktadır (2). Yaşam süresinin ve kalitesinin artması sistemik hastalığı bulunan hastalar ile diş hekimlerinin karşılaşma insidansını artırmaktadır (1). Sistemik hastalığı olan hastaların dental girişimlere karşı toleransı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 4 publications
2
2
0
Order By: Relevance
“…In addition, in this study, the frequency of malignant disease was 1.52%, transplantation patient 0.22% and neurological and psychiatric diseases 1.6%. Similar to this study, Ciğerim et al 19 study found that neurological and psychiatric diseases were less common in patients who applied for dental treatment. Additionally, the rate of malignant disease and organ failure has been reported to be 0.4%.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In addition, in this study, the frequency of malignant disease was 1.52%, transplantation patient 0.22% and neurological and psychiatric diseases 1.6%. Similar to this study, Ciğerim et al 19 study found that neurological and psychiatric diseases were less common in patients who applied for dental treatment. Additionally, the rate of malignant disease and organ failure has been reported to be 0.4%.…”
Section: Discussionsupporting
confidence: 87%
“…The present study revealed that the second most common disease was endocrine system disease, and diabetes was the most common disease among them. In parallel with this study, it has been reported that the second most common endocrine system diseases are in the studies of Ciğerim and Aggarwal et al 19,26 . Dental practitioners should know that diabetes mellitus may cause oral symptoms such as burning sensation in the mouth, candidiasis, cariosity, lichen planus, dysesthesia, and saliva function disorder 27 .…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations